THE CAUSES STUDY OF THE PREMATURE DESTRUCTION OF THE CONCRETE SLEEPERS ON THE ZNAMENKA TRACK OF THE IF10 OF THE ODESSA RAILWAY - Kovalenko, V. V.; Zayats, Y. L.; Pshinko, P. O. (Science and Transport Progress, 2015)
Purpose. The aim of the paper is to study the factors that led to the premature destruction of concrete sleepers. Methodology. The express-method of determining the morphology and chemical composition of structural components in concrete, patented by Dnipropetrovsk National University of Railway Transport was used in the paper. Methodology makes it possible to control the morphology and chemical composition of cement crystals as the weakest link in the structure of composite material – concrete, and to predict, in accordance with the recommendations of the German Scientists, the possibility of structural transformation of cement in the solid state, which determines the durability of the composite material. Findings. The mass destruction of concrete sleepers on railways of Ukraine is becoming more frequent every year. Moreover, if such destruction in 2010 appears after 4-5 years of operation, in 2015 it is only after 2-3 years of installing the sleepers on the main railways. The nature of the destruction of concrete sleepers can be noted as malty factors influence on it. The batches of cement and other raw materials have been investigated before using with the standard methods in accredited laboratories of PAC «Ukrgeolbudm» (Kyiv) and received a positive evaluation for use in the production of concrete sleepers. However, a significant error in experimental data by standard methods not allowed revealing the critical properties of materials that adversely effect on the durability of rail base concrete. According to the research it was determined that the causes of mass destruction of sleepers are: 1) the inhomogeneity of the macrostructure of the concrete, as a consequence of the use of crushed rock of fraction 5-25 mm; 2) the impact of aggressive environment on the surface of the concrete sleepers; 3) the presence of a secondary structure of sleepers of large ettringite crystals prone to restructuring and the presence of alkaline silicic acid reaction products around the amorphous or those containing amorphous silica sand particles; 4) the exceeding of regulatory factor of the reduced alkalinity of dense and porous components of cement stone is respectively to 3.6 and 3.2 times; 5) saturation of the surface of sand particles of chlorine atoms, which are further accelerate and initiate the alkaline silicic acid reaction. Originality. The scientists firstly applied the author’s proprietary express-method of studying the morphology and chemical composition of the structural components of concrete. Practical value. The application of the proposed research methodology and structure of raw materials in the concrete production cycle of enterprises will help to prevent the premature deterioration of concrete as a result of internal factors.